Self-referencing versus other-referencing in gambling: effects of vmPFC stimulation on decision-making and feedback processing - Kroker, Thomas; Rehbein, Maimu Alissa; Wyczesany, Miroslaw; Hansen, Selina; Bianco, Riccardo; Espino-Paya, Alejandro; Junghöfer, Markus (Frontiers in Behavioral Neuroscience, 2025)
IntroductionA key skill useful in everyday life is learning from our past choices to overcome cognitive biases and cope with our environment. In this regard, we are often responsible not only for ourselves but also for others.MethodsAs our previous results showed that after excitatory stimulation of the ventromedial prefrontal cortex (vmPFC) people improved risk weighing and reduced their cognitive biases via improved affective learning, here we examined whether the above results differ when participants are playing for themselves versus for someone else. Therefore, we added this experimental manipulation to our previously well-validated gambling paradigm.ResultsWe found that participants showed improved learning after excitatory stimulation when playing for themselves but not when playing for someone else. At the neural level, we observed interaction effects involving the stimulation (inhibitory vs. excitatory), the frame (gain vs. loss) and the recipient (self vs. other) in prefrontal, temporal and parietal areas during the decision-making and feedback phase.DiscussionOur results suggest that excitatory vmPFC-tDCS can facilitate gambling and enhance the neural processing of gambling-related stimuli when playing for oneself.